Ability of Evaluation Coronary Calcium Index Based on Ultra-Low-Dose Computed Tomography Used in Moscow Lung Cancer Screening Project - A. E. Nikolaev; A. N. Shapiev; O. A. Korkunova; G. Z. Mukhutdinova; P. V. Tkacheva; M. M. Suleymanova; A. N. Shapieva; D. M. Ramazanova; M. N. Rzayev; V. A. Gombolevsky (Рациональная фармакотерапия в кардиологии, 2021)
Aim. Determination of the possibility of reliable quantitative assessment of the coronary calcium index based on ultra-low-dose computed tomography (ultra-LDCT) which used in Moscow Lung Cancer Screening project.Material and methods. The study included the results of 254 ultra-LDCT studies conducted as part of the Moscow lung cancer screening project. For compare the parameters of coronary calcium on different images used 16 pairs of ultra-LDCT images with a slice thickness of 1 mm and CT images with a slice thickness of 3 mm, performed without ECG synchronization, performed with an interval of less than 10 days, as well as 18 pairs of ultra-LDCT with a slice thickness of 1 mm and CT with ECG synchronization with a slice thickness of 3 mm, performed on the same day after execution. Analysis of DICOM 3.0 standard images was performed. Quantitative indicators of coronary calcium in patients from lung cancer screening were analyzed, a comparative analysis of the calcium index for Agatstone, Volume, Mass, and using the CAC-DRS scale (assessment of the degree of calcification by scores from 0 to 3 and the number of affected arteries from 0 to 4 points) was performed.Results. Evaluation ultra-LDCT with a slice thickness in 1 mm and with a CT scan with slice thickness in 3 mm with and without ECG-synchronization for the presence of coronary calcium, and subsequent rating according to the index Agatston, Volume, Mass, as the total coronary calcium and for each coronary artery (right, left, left descending, left circumflex) received the complete data correlation (Pearson's - 1), with full correlation (Spearman's >0.9), with good rank correlations (>0,9). Compare qualitative (CAC-DRS V) and quantitative (CAC-DRS A) estimates on ultra-LDCT with CT with ECG synchronization in the same patients show a complete correlation of data was obtained (Pearson's formula - 1), with a complete correlation (Spearman's formula - 1).Conclusion. Coronary calcium which detected in lung cancer screening subjects should be included in the overall decision-making process for further routing of patients (cardiologist, interventional surgeon, pulmonologist, therapist). Ultra-LDCT is a method that has high diagnostic accuracy in detecting and evaluating the prevalence of coronary calcium in comparison with standard CT with and without ECG synchronization, as demonstrated in our study. Evaluation of coronary calcium according to ultra-LDCT without ECG synchronization used in screening, preferably with a 1 mm slice thickness. Despite the fact that the gold standard is CT with ECG synchronization with a 3 mm slice thickness, the diagnostic significance of ultra-LDCT which used in lung cancer screening is high in relation to detecting coronary artery calcification.